Pengembangan LKPD Berbasis Uang Mainan untuk Pembelajaran Persentase dengan Pendekatan PMRI - Miranti Miranti; Salsa Ameylia Zahra; Syutaridho Syutaridho (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study aims to describe the process of learning mathematics on percentage material through the use of play money with the Indonesian Realistic Mathematics Education (PMRI) approach in class VII SMP. The PMRI approach is used to link mathematical concepts with real contexts, in this case buying and selling activities using play money. This research is a descriptive qualitative research conducted at MTs Al-Mu'aawanah Pemulutan, Ogan Ilir. The research subjects were seventh grade students. The instruments used include Learner Worksheets (LKPD), observation, and interviews. The results showed that the use of play money can help students understand the concept of percentage more concretely and contextually. Students become more active in the learning process and are able to connect the concept of percentage with everyday situations. The PMRI approach proved to be effective in increasing students' engagement and understanding of percentage material.